Unveiling Baghdad's Urban Identity: A Comprehensive Study on the Dynamics of Urban Imprint - Abbas, Asawer Abdulrahman; Hussein, Shaimaa Hameed (Universitas Muhammadiyah Sidoarjo, 2024)
This research examines the